A Novel Strategy to Improve Crop Productivity under Sustainable Agriculture - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2012)
Shift in crop ecology due to climate change is a major concern for world’s food production. It is predicted that global warming is going to be a major challenge for future crop improvement programmes. It is associated with several abiotic stresses such as heat, drought, flooding and salinity are threatening food security and drastically reducing crop productivity under sustainable agriculture. Therefore, there is a great necessity of scientists to develop strategy for combating these menaces. The objective of this paper is to develop new technologies for selecting crops for tolerance to various abiotic stresses. Concerted efforts have been directed by scientists to evaluate world germplasms to select crop genotypes tolerant to various abiotic stresses and finally selected cultivars with high tolerance but with poor agronomic background. Resistance to biotic and abiotic stress is negatively related to yield. In this respect, insignificant progress has been achieved to increase production under sustainable agriculture in farmers. Therefore, there is a need to adopt a new strategy for increasing crop production under sustainable agriculture. This paper addresses to put forward novel strategies and developing technologies from pipe line hybrids. Here, author described simple, efficient and cheap techniques for identifying tolerant lines of several fields including few vegetable crops for several abiotic stresses such as drought, salinity, flooding etc. The strategy is outlined by developing new efficient technologies (standardization and testing its reliability), screening and selecting pipeline hybrids and varieties, confirming the selected lines in the field under stress conditions and transfer of technology from lab to land.